2016
DOI: 10.1002/bjs.10283
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of sentinel lymph node biopsy in breast cancer using the magnetic technique

Abstract: The magnetic technique for SLNB is non-inferior to the standard technique, with a high identification rate but with a significantly higher lymph node retrieval rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 30 publications
3
44
0
3
Order By: Relevance
“…One of the possible approaches to replace the method based on a radioactive tracer is the use of magnetic nanoparticles with a magnetic probe detection system, which has been compared in various clinical studies that have shown promising results . A meta‐analysis of SLNB clinical trials using the magnetic detection system demonstrated that the SLN identification rate was not inferior to that of simultaneous administration of radioactive colloids +/− dye (conventional method vs magnetic method: 96.8% vs 97.1%) . In Europe, Sienna+ has obtained CE mark approval as magnetic nanoparticles, while Sentimag has obtained CE mark approval as a magnetic probe.…”
Section: Introductionmentioning
confidence: 99%
“…One of the possible approaches to replace the method based on a radioactive tracer is the use of magnetic nanoparticles with a magnetic probe detection system, which has been compared in various clinical studies that have shown promising results . A meta‐analysis of SLNB clinical trials using the magnetic detection system demonstrated that the SLN identification rate was not inferior to that of simultaneous administration of radioactive colloids +/− dye (conventional method vs magnetic method: 96.8% vs 97.1%) . In Europe, Sienna+ has obtained CE mark approval as magnetic nanoparticles, while Sentimag has obtained CE mark approval as a magnetic probe.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic technique has now been evaluated in a number of studies and confirmed on meta-analysis to be noninferior to the radioisotope-dependent technique in breast cancer -with sentinel node identification rates of 97.1 and 96.8%, respectively [3] -and demonstrated technical benefits over other novel techniques [4]. The noninferiority of the magnetic technique has also been demonstrated in the staging of malignant melanoma [5] and has been applied to a range of solid cancers in small cohort series, which has demonstrated its feasibility in the staging of these malignancies [6][7][8].…”
Section: Magnetic Technique For Snbmentioning
confidence: 99%
“…Blue dye is also associated with prolonged skin staining and reports of anaphylaxis in 0.9% of patients [2]. These limitations have resulted in the on-going development of alternative techniques for SNB [3,4]. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Риск лимфогенной диссеминации опухоли при РШМ IA стадии в регионарные лимфати-ческие узлы составляет 2,8 -4,8 %, при IB -13,6 -15,9 %, тактика лечения может быть основана на результатах экспресс-морфологического, или послеоперационного исследования удаленных лимфатических узлов [5]. Мно-гие авторы справедливо подчеркивают, что удаление лимфатических узлов не приносит пользу большинству пациенток с начальными стадиями рака шейки матки.…”
unclassified